Aspergillus aculeatus enhances nutrient uptake and forage quality in bermudagrass by increasing phosphorus and potassium availability - Li, Xiaoning; Zhang, Ting; Xue, Ying; Xu, Xiao; Cui, Xinyu; Fu, Jinmin (Frontiers in Plant Science, 2023)
Potassium and phosphorus are essential macronutrients for plant growth and development. However, most P and K exist in insoluble forms, which are difficult for plants to directly absorb and utilize, thereby resulting in growth retardation of plants under P- or K-deficiency stress. The Aspergillus aculeatus fungus has growth-promoting characteristics and the ability to dissolve P and K. Here, to investigate the physiological effects of A. aculeatus on bermudagrass under P or K- deficiency, A. aculeatus and bermudagrass were used as experimental materials. The results showed that A. aculeatus could promote tolerance to P-deficiency or K-deficiency stress in bermudagrass, decrease the rate of leaf death, and increase the contents of crude fat as well as crude protein. In addition, A. aculeatus significantly enhanced the chlorophyll a+b and carotenoid contents. Moreover, under P- or K-deficiency stress, bermudagrass inoculated with A. aculeatus showed higher N, P and K contents than noninoculated plants. Furthermore, exogenous A. aculeatus markedly decreased the H2O2 level and CAT and POD activities. Based on our results, A. aculeatus could effectively improve the forage quality of bermudagrass and alleviate the negative effects of P or K-deficiency stress, thereby playing a positive economic role in the forage industry.